Advances in the Diagnosis and Treatment of Tuberculosis - Nahid, Payam (American Thoracic Society, 2006)
Although truly major advances that would revolutionize tuberculosis (TB) diagnosis and treatment have not been realized, we are beginning to see the innovations that have been prompted by the recognition of the economic potential of the market for new diagnostic tests and treatments for TB and considerably increased public and private funding. Despite the enormous global burden of TB and the overall low rates of case detection worldwide, conventional approaches to diagnosis have, until recently, relied on tests that have major limitations. In this review of advances in diagnosis, we focus on strengths and limitations of newer tests that are available for the diagnosis of latent and active tuberculosis and rapid detection of drug resistance, specifically, tests that measure release of IFN-γ in response to stimulation by Mycobacterium tuberculosis antigens, nucleic acid amplification for identification of M. tuberculosis complex, and rapid tests for detecting drug resistance. Standard regimens for treating TB have not changed for more than 30 yr and still require a minimum of 6 mo to have a high likelihood of a lasting cure. In this article, we focus on important changes in the philosophy of treatment, emphasizing the responsibility of the provider to assure successful completion of treatment, and on the roles of existing anti-TB agents and newer drugs such as rifabutin, rifapentine, and fluoroquinolones.